Analisis Intellectual Capital Terhadap Kinerja Perusahaan (Study Kasus Bank Perkreditan Rakyat (BPR) di Kepulauan Riau) - Efriyenti, Dian; E Janrosl, Viola Syukrina (Jurnal Ilmiah Professional Indonesia, 2017)
Bank (BPR) is one of the important backbone in national development. In recent years the number of BPR has decreased. Until October 2011, the number of conventional BPRs in the whole of Indonesia BPR activities often forget about Corporate Social Responsibility, Environment, and Intellectual Capital programs. As in the case of BPRs in Lampung who went bankrupt and in Solo BPR Fires Office. Research location in this research will be done in Batam city. Riau Islands Province, with the research object of Rural Bank. The population used in this research is the Rural Bank in Riau Islands, amounting to 41 BPRs located in Riau Islands and registered in the report of Bank Indonesia. While the sample used in this study is the accounting staff of Rural Banks operating in Riau Islands. The data used in this research are primary data and secondary data. Primary data is data obtained from questionnaires and in this research. The secondary data used is sourced from Bank Indonesia and Rural Bank (BPR) as sample in the research. Result of research of human capital, structural capital and relational capital will increase from company performance which closely related to human resources owned by company. The results of simultaneous research intellectual capital plays an important role in the financial performance of Rural Banks because there are indications of the use of physical assets (remain) that still dominate to contribute to the performance of the company. Bank Perkreditan Rakyat (BBPR)) merupakan salah satu tulang punggung penting dalam pembangunan nasional.. Dalam beberapa tahun terakhir jumlah BPR telah menurun.. Hingga Oktober 2011,, jumlah BPR konvensional di seluruh kegiatan BPR di Indonesia sering melupakan program Corporate Social Responsibility,, Environment,, dan Intellectual Capital.. Seperti kasus BPR di Lampung yang bangkrut dan di Kantor BPR Solo.. Lokasi penelitian dalam penelitian ini akan dilakukan di kota Batam.. Provinsi Kepulauan Riau,, dengan objek penelitian BPR.. Populasi yang digunakan dalam penelitian ini adalah BPR di Kepulauan Riau,, sebesar 41 BPR yang berada di Kepulauan Riau dan terdaftar dalam laporan Bank Indonesia.. Sedangkan sampel yang d igunakan dalam penelitian ini adalah staf akuntansi BPR yang beroperasi di Kepulauan Riau.. Data yang digunakan dalam penelitian ini adalah data primer dan data sekunder.. Data primer adalah data yang diperoleh dari kuesioner dan dalam penelitian ini.. Data sekunder yang digunakan bersumber dari Bank Indonesia dan BPR sebagai sampel dalam penelitian ini.. Hasil penelitian modal manusia,, modal struktural dan modal relasional akan meningkat dari kinerja perusahaan yang terkait erat dengan sumber daya manusia yang dimiliki oleh perusahaan.. Hasil penelitian serentak modal intelektual memegang peranan penting dalam kinerja keuangan BPR karena ada indikasi penggunaan aset fisik (ttetap)) yang masih mendominasi memberikan kontribusi terhadap kinerja perusahaan..